The Clinical Significance of Tumor MIR-122, -155, -182, and -200b Expression in Patients with Breast Cancer - Chekhun, V.F.; Lukianova, N.Yu.; Borikun, T.V.; Bezdenezhnykh, N.A.; Shepelenko, I.V.; Bazas, V.M.; Klyusov, A.N. (Science and Innovation, 2024)
The research was aimed at identifying the relationship between the oncogenic (-182, -155) and the onco-suppressive (-122, -200b) microRNAs in tumor cells with clinical and pathological characteristics of breast cancer (BC) and at establishing their clinical significance. MicroRNA levels have been determined by reverse transcription polymerase chain reaction (RT-PCR) in real time. The expression of estrogen (ER) and progesterone (PR) receptors, and Her2/neuepidermal growth factor has been ascertained by immunohistochemical method. The relationship of these microRNAs expression with the disease stage, the presence of metastatic lesions of regional lymph nodes, the differentiation degree, and the tumor molecular subtype has been established. The obtained results have confirmed the involvement of the tested microRNAs in the formation of BC malignancy degree, their association with tumor aggressiveness and have defined the prospects of further studies of the proposed microRNAs panel for their use as BC additional markers.